Energy conservation and renewable technologies for buildings to face the impact of the climate change and minimize the use of cooling. (15th September 2017) - Ascione, Fabrizio
Graphical abstract: Highlights: The future target of net and nearly zero-energy buildings does not mean mitigation of UHI effect. In order to face the climate change and contrasting global warming, the reduction of cooling need is needed. Two approaches are possible: defense from the ambient or interaction between building and surroundings. Solar screens, cool colors, thermal mass, natural ventilation reduce the cooling need. Ground, evaporative, solar and passive cooling improve the summer comfort. A large literature review, concerning building envelope, HVAC systems and renewables is proposed. Abstract: Facing the climate change is a common priority, due to ethical issues related to general concept of sustainability and livable future for the next generations. Moreover, ethical aims for contrasting energy poverty, heat-related diseases and deaths, availability of food and water, infections and viral-bacteriological risks, meteorological extreme phenomena, such as floods and intense and destructive precipitations, are stringent and pressing targets. All serious and independent investigations reveal future scenarios of an overall global warming that surely make worrying the evolution of quality of life on this earth. Each one has to do his part. In this study, the research is focused on renewable technologies for the passive cooling of buildings. Indeed, the space cooling is a strongly increasing use of energy and induces a vicious circle, being, at the same time, a cause and an effect of the anthropogenic overheating of the planet. The paper mainly reviews techniques for suitably governing the energy interaction between buildings and surrounding environment. The energy efficiency concerns the building envelope design, the use of efficient HVAC systems, adoption of renewable energy on-site. On the other hand, every energy conversion process determines waste heat, so that also a 'free of operational cost' solar cooling system however causes dissipation of heat into the ambient. Finally, renewables cannot be the unique solutions for supplying the energy required for the building use. Conversely, strategies for reducing the building cooling are needed, and these are reviewed in this study. In thermodynamics terms, the building is seen as part of the system and not the mere control volume. Greenery of facades and roofs, phase change materials, nocturnal convective cooling, evaporative and ground cooling, solar systems such as chimneys for improving the building ventilation are here discussed, as well as emerging technologies such as breathing walls and dynamic insulation. The reviewed studies, selected on the basis of more recent progresses concerning the investigated technologies, revealed potentialities but also criticalities in the design.